2012
DOI: 10.1007/s10875-012-9663-6
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Tolerance Defects in the B6.Aec1/2 Mouse Model of Sjögren’s Syndrome

Abstract: Purpose Primary Sjögren’s syndrome (SjS) is an autoimmune disorder characterized by lymphocytic infiltration of the salivary and lacrimal glands, B-cell clonal expansions and an increased risk of lymphoma. In order to understand the role of B cells in this disorder, the antibody repertoire and B-cell maturation were studied in a mouse model of SjS called B6.Aec1/2. Methods B6.Aec1/2 serum was analyzed for (auto)antibodies by ELISA and immunoprecipitation, B-cell development by flow cytometry, antibody gene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The involvement of B cells in SS is well established, as SS patients have B cell infiltration in salivary and lacrimal glands in humans and rodents. SS patients have an increased risk for non-Hodgkin lymphomas (93)(94)(95)(96). The role of B cell receptor signaling in the conjunctiva of SS KCS patients has not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of B cells in SS is well established, as SS patients have B cell infiltration in salivary and lacrimal glands in humans and rodents. SS patients have an increased risk for non-Hodgkin lymphomas (93)(94)(95)(96). The role of B cell receptor signaling in the conjunctiva of SS KCS patients has not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Many mouse studies have identified defects in B cell central tolerance, in terms of either receptor editing or clonal deletion, in spontaneous models of SLE 107,108 , Sjogren syndrome 109 and type 1 diabetes 110 , although there is as yet no real consensus as to the mechanisms involved. As editing can both destroy and create certain autoantibody specificities, insufficient as well as excessive editing may be deleterious 111,112 .…”
Section: Superantigen Screens For Tolerance Genesmentioning
confidence: 99%
“…Transfer of wild type T cells into young NOD IL-4 knockoutmice reconstituted the production of anti-M3R autoantibodies and subsequent decline in salivary secretory activity. In the related, NOD-derived Aec1/Aec2 model, glandular disease is preceded by the appearance in spleens and lymph nodes of activated CD4+ T cells bearing markers of effector-memory cells [49]. These cells are present before the appearance of activated B cells and autoantibodies and before salivary flow is reduced.…”
Section: Lessons From Ss Animal Modelsmentioning
confidence: 99%